De Novo Diagnosis of Lymphocytic Colitis After SARS-CoV-2 Vaccination. Issue 9 (7th September 2022) - Lee, Preston; Wei, Mike T.; Gubatan, John; Forgó, Erna; Berry, Gerald J.; Verma, Rahul; Friedland, Shai
ABSTRACT: SARS-CoV-2 mRNA vaccines are safe and effective for most patients. Gastrointestinal complications reported after vaccination have included gastroparesis and inflammatory bowel disease flares. In this study, we present a unique case of lymphocytic colitis that occurred in a healthy middle-aged man after Moderna SARS-CoV-2 mRNA vaccination. This reveals an unexpected complication of a mRNA vaccine that presented as worsening diarrhea after vaccination in a dose-dependent pattern. Caregivers should be aware of lymphocytic colitis as a possible complication of the Moderna vaccine and monitor those patients closely for symptom resolution.